Soft Masculinity dan Female Gaze pada Iklan Mirael Sugar Wax x Jefri Nichol “Waxing Itu Enak, Waxing Itu Mirael, Nagih Kan?” - Rifki Aris Sandi; Reiner Christlouvie Lomanto; Rama Narendra; Favian Daffa Gusma (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2026)
This study explores how the Mirael Sugar Wax x Jefri Nichol advertisement titled “Waxing Itu Enak, Waxing Itu Mirael, Nagih Kan?” constructs soft masculinity while mobilizing the female gaze as a commercial strategy. The analysis focuses on a single video advertisement, examining frame composition, gaze direction, bodily gestures and facial expressions, vocal intonation, lighting, background color, and the interaction between visual and audio elements in producing meaning. Using Multimodal Discourse Analysis, the study finds that Jefri Nichol’s body is presented as sensual and aesthetically appealing, open to being looked at, yet still maintaining symbolic control through his athletic physique and carefully managed performance. This representation does not fully challenge patriarchal structures; instead, it offers a softer and more flexible form of masculinity that remains within the same framework of power. In this context, the female gaze does not operate as a reversal of dominance but as a contemporary way of packaging and marketing the male body within visual consumer culture. The study contributes to masculinity and advertising scholarship in Indonesia by demonstrating how male objectification can function as a market strategy that reshapes masculine imagery without fundamentally disrupting dominant gender arrangements.Penelitian ini membahas bagaimana iklan Mirael Sugar Wax x Jefri Nichol berjudul “Waxing Itu Enak, Waxing Itu Mirael, Nagih Kan?” membangun representasi soft masculinity sekaligus memanfaatkan female gaze sebagai strategi komersial. Analisis dilakukan terhadap satu video iklan dengan menelaah komposisi gambar, arah tatapan, gestur dan ekspresi tubuh, intonasi suara, pencahayaan, warna latar, serta hubungan antar unsur visual dan audio yang membentuk makna. Melalui pendekatan Multimodal Discourse Analysis, penelitian ini menunjukkan bahwa tubuh Jefri Nichol ditampilkan sebagai sosok yang sensual dan estetis, terbuka terhadap tatapan, tetapi tetap memegang kendali simbolik melalui tubuh yang atletis dan performa yang terkontrol. Representasi ini tidak benar benar menggugat struktur patriarki, melainkan menampilkan bentuk maskulinitas yang lebih lembut dan lentur namun tetap berada dalam kerangka kuasa yang sama. Female gaze dalam iklan ini bekerja bukan sebagai pembalikan dominasi, tetapi sebagai cara baru untuk mengemas dan menjual tubuh laki laki dalam budaya konsumsi visual. Temuan ini memberi sumbangan pada kajian maskulinitas dan periklanan di Indonesia dengan menunjukkan bahwa objektifikasi laki laki dapat menjadi strategi pasar yang memperbarui citra maskulinitas tanpa sepenuhnya menggeser tatanan gender yang dominan.